PENGARUH KONSELING REALITA TERHADAP ADAPTATION DAN RESPONSIBILITY MAHASISWA STIKes SANTA ELISABETH MEDAN - Mestiana Br Karo; Murni Sari Dewi Simanullang; Mariska Regina (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
The first year student will face various challenges in the college where he studies. The challenge is due to changes in the environment, different ways of learning, and adjustments to friends with different backgrounds and ethnicities. If students are unable to accept this reality, it will have an impact on their ability to adapt and take responsibility for completing their lectures. Reality counseling using WDEP techniques can help a person to have effective behavior. The WDEP technique refers to four strategy groups namely Want, Doing, Evaluation, and Plan. The purpose of this study was to analyze the effect of WDEP technique reality counseling on student adaptation and responsibility. From 33 midwifery level 1 students at STIKes Santa Elisabeth Medan, a simple random sampling was conducted and 10 study respondents were obtained. The research design used in this study was pre experimental one group pre post test design. The instrument used in this study was a questionnaire consisting of 13 statements for adaptation and 13 statements for responsibility. Reality counseling is conducted four times, with a duration of 45 minutes for each meeting. Data analysis was performed with the Fisher Exact test with the results of p value = 0,000 (p <0.05) which showed a significant effect on the reality of WDEP technique counseling on adaptation and responsibility of midwifery level 1 students at STIKes Santa Elisabeth Medan. The results of this study are expected to be input for educational institutions to provide WDEP technical reality counseling to first-degree students.